2004
DOI: 10.1111/j.1582-4934.2004.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione depletion‐induced chromosomal DNA fragmentation associated with apoptosis and necrosis

Abstract: Chromosomal DNA and mitochondrial dysfunctions play a role on mammalian cell death induced by oxidative stress. The major biochemical dysfunction of chromosome is the presence of an ordered cleavage of the DNA backborn, which is separated and visualized as an electrophoretic pattern of fragments. Oxidative stress provides chromatin dysfunction such as single strand and double strand DNA fragmentation leading to cell death. More than 1 Mb of giant DNA, 200-800 kb or 50-300 kb high molecular weight (HMW) DNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(116 citation statements)
references
References 48 publications
14
96
0
6
Order By: Relevance
“…Accordingly, our study demonstrates that alantolactone treatment increases the expression of p53 in U87 cells in a time-dependent manner. Other studies have shown that GSH depletion can directly modulate MMP, Bax translocation, and caspases activation, resulting in activation of mitochondrial death cascade (10,29). In this study, alantolactone disrupted MMP and increased the expression of Bax accompanied by a decrease in Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 55%
“…Accordingly, our study demonstrates that alantolactone treatment increases the expression of p53 in U87 cells in a time-dependent manner. Other studies have shown that GSH depletion can directly modulate MMP, Bax translocation, and caspases activation, resulting in activation of mitochondrial death cascade (10,29). In this study, alantolactone disrupted MMP and increased the expression of Bax accompanied by a decrease in Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 55%
“…This oxidative assault to cells could lead to a decrease in cell proliferation or even leading to cell death via an apoptotic pathway or by necrosis. [13][14][15] To further assess the extent of damage as a result of oxidative assault by SWCNT particles, cell viability was determined after exposing the cells to various concentrations of SWCNT particles. Cytotoxicity was assayed by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT, Sigma, St. Louis, MO) dye uptake as described by Manna et al 16 Briefly, HaCaT cells (10 4 cells/well of 96-well plate) were incubated with SWCNT particles in a final volume of 0.1 mL for 72 h at 37 °C.…”
Section: Swcnt Particles Induce Oxidative Stress and Inhibit Cell Promentioning
confidence: 99%
“…The nuclear GSH pool is thought to be maintained by the diffusion of GSH into the nucleus across nuclear pores. 66,67 Conjugation of GSH is an essential aspect of xenobiotic and normal physiological metabolism. The glutathione S-transferases (GST) form a class of enzymes with overlapping substrate specificities that generate a large set of thioesthers, called glutathione S-conjugates.…”
Section: Figure 1 Apoptotic Signaling Pathways (See Text For Further mentioning
confidence: 99%